Адміністративно-правові механізми протидії торгівлі людьми в контексті захисту прав і свобод громадян України за кордоном - Фелонюк, Д.; Feloniuk, D. (Східноєвропейський національний університет імені Лесі Українки, 2019)
Проаналізовано національний механізм взаємодії суб’єктів, які здійснюють заходи по захисту прав та свобод громадян України за кордоном. Розглядаються особливості застосування поняття «торгівля людьми» в праві. Досліджуються масштабність проблеми та напрямки її вирішення з врахуванням європейського досвіду. Звертається увага на необхідність тісної координації дій вітчизняних та міжнародних інституцій по попередженню та захисту громадян України від торгівлі людьми, боротьбою зі злочинністю пов’язаної з цими протиправними діями.The article elucidates features of the national mechanism of interaction of the subjects carrying out measures to protect the rights and freedoms of the Ukrainian citizens abroad. The basis for the study is the rules of the concept of «human trafficking» interpretation in law. The magnitude of the problem and the directions of its solution are considered, taking into account the European experience. The author argues the need for close coordination of the actions of national and international institutions to prevent this evil, protect the Ukrainian citizens from trafficking, and to combat the crimes associated with these illegal actions. The study findings manifest that the national administrative and legal mechanism for combating human trafficking provides a system of measures to detect the crime of human trafficking, to identify the persons involved in its commission, and how to bring them to justice. The effectiveness of this mechanism, to a large extent, depends on the interaction and coordination of actions between national and international institutions dealing with human trafficking. The facilitating factors are the integration of Ukrainian legislation into European law, the cooperation between state and non-state subjects, participating in combating human trafficking.
Administrative and Legal Mechanisms for Combating Human Trafficking in the Context of Protecting the Rights and Freedoms of Citizens of Ukraine Abroad
Keywords: торгівля людьми; права; свободи; громадянин; Україна; human trafficking; rights; freedoms; citizen; Ukraine